Pengaruh Citra Merek dan Inovasi Produk terhadap Keputusan Pembelian Skincare Kahf - Luthfy Adhitya Wahyu Ananda; Yenny Del Rosa (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the influence of brand image and product innovation on purchasing decisions of Kahf skincare among students of the Faculty of Economics and Business, Dharma Andalas University. The research method used is quantitative with a total sampling technique involving 157 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that brand image and product innovation have a positive and significant effect on purchasing decisions. A strong brand image enhances trust and purchase intention, while product innovation drives satisfaction and repurchase intention.